The Establishment of the GNAT in the Russian Press - (:unkn) unknown (AHMET YESEVI UNIV, 2021)
The Grand National Assembly of Turkey (GNAT) is celebrating its 100th anniversary. Therefore, it is beneficial to clarify the details of the establishment of the GNAT. The issue of how the establishment of the GNAT was reflected in the Russian press has not been investigated so far. The Bolshevik Russian press closely followed the developments in Anatolia as they wanted to see the national campaign in Anatolia as the struggle of the Turkish Bolsheviks against imperialism. In this study, we have tried to collect the information directly or indirectly related to the GNAT in the Russian press between 1919 and 1920 chronologically and to reflect what the GNAT meant for the Bolsheviks.
Keywords: Russian Press; GNAT; Mustafa Kemal; National Campaign; Ankara